2020
DOI: 10.48550/arxiv.2012.04435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability of the Gel'fand inverse boundary problem via the unique continuation

Abstract: We prove an explicit estimate on the stability of the unique continuation for the wave operator on compact Riemannian manifolds with smooth boundary. Our estimate holds on domains arbitrarily close to the optimal domain, and is uniform in a class of Riemannian manifolds with bounded geometry. As an application, we obtain a quantitative estimate on the stability of the Gel'fand inverse boundary problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 22 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…It was shown in [57] that inverse boundary spectral problems are equivalent to inverse problems for the wave and heat equations in the time domain. The stability of the solutions of these inverse problems have been analyzed in [1,20,25,43,81]. Numerical methods to solve the Gel'fand's inverse problems have been studied in [13,40,41].…”
Section: Earlier Results and Related Inverse Problemsmentioning
confidence: 99%
“…It was shown in [57] that inverse boundary spectral problems are equivalent to inverse problems for the wave and heat equations in the time domain. The stability of the solutions of these inverse problems have been analyzed in [1,20,25,43,81]. Numerical methods to solve the Gel'fand's inverse problems have been studied in [13,40,41].…”
Section: Earlier Results and Related Inverse Problemsmentioning
confidence: 99%
“…Under such type of conditions, invariant stability results for various inverse problems have been proven in [5,29,75,76]. In particular, for the inverse interior spectral problem on manifolds with non-trivial topology, stability results have been obtained in [5,9], see also [14] for analogous results for manifolds with boundary. In the latter, it was shown that the convergence of the boundary spectral data implies the convergence of the manifolds with respect to the Gromov-Hausdorff distance.…”
Section: 34mentioning
confidence: 99%
“…Tataru's unique continuation theorem is crucial for the Boundary Control method in solving inverse problems for linear equations, see e.g. [3,7,13,14,26,28,29]. The unique continuation for linear systems of hyperbolic equations was studied in [21], and the result can be applied to the time-dependent classical elasticity system and the Maxwell system.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by Tataru's ideas in [44], the quantitative stability of the unique continuation for the wave operator was obtained by [11,12] and [30] independently. An explicit stability of the unique continuation on Riemannian manifolds with boundary was recently obtained by [14], with U being a subset of the boundary. In this paper, we study the explicit stability of the unique continuation for a linear system of hyperbolic equations on Riemannian manifolds with boundary, with U being an interior open subset of the manifold.…”
Section: Introductionmentioning
confidence: 99%